From Thumbelina to Winnie-the-Pooh: Pictures, Words, and Sounds in Translation - Oittinen, Riitta (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThe starting point of my article is that even though words are translators’ tools, the texts they translate often include images, sounds, and movement, too. In other words, translators need media literacy. In the following, I discuss translating picturebooks and films, using different retellings of Disney and Andersen as examples. In addition, I ponder on issues such as text and situation as well as the interaction of the verbal, visual and aural information in the context of translation.